Advances in pharmacology. - Liu, Leroy F. (Advances in pharmacology (San Diego, Calif.) ;, 1994)
Each volume of Advances in Pharmacology provides a rich collection of reviews on timely topics. Emphasis is placed on the molecular basis of drug action, both applied and experimental.